2022
DOI: 10.1111/cod.14260
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and relevance of patch testing with textile dyes

Abstract: Background Textile dye mix (TDM) is included in the European baseline series (EBS), but it is unknown if TDM identifies all patients with a textile dye allergy. Objectives To assess the added value of performing patch testing with individual textile dyes in addition to TDM. Methods Two hundred and nine patients suspected to have a contact allergy to textile dyes were patch tested between January 2015 and December 2021 with the EBS, as well as an individual textile dye test series containing textile dyes part o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…The research of Stingeni et al 11 is the only one with a low proportion of concomitant positivity between TDM and PPD (28.5%). The vast majority of studies show that, similar to our results, simultaneous positivity between TDM and PPD is common, as it is between DO 3 and PPD, and vice versa 6–9,11,12,17 . In the study of Isaksson et al, 12 61% of TDM‐allergic patients were also allergic to PPD and 75% to any separate DDs, DO 3 being the most frequent.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The research of Stingeni et al 11 is the only one with a low proportion of concomitant positivity between TDM and PPD (28.5%). The vast majority of studies show that, similar to our results, simultaneous positivity between TDM and PPD is common, as it is between DO 3 and PPD, and vice versa 6–9,11,12,17 . In the study of Isaksson et al, 12 61% of TDM‐allergic patients were also allergic to PPD and 75% to any separate DDs, DO 3 being the most frequent.…”
Section: Discussionsupporting
confidence: 89%
“…In contrast, Stingeni et al 11 observed a higher clinical relevance of 70%. Concerning studies in selected patients with suspected textile ACD, Nijman et al 17 observed that most cases were linked to clinical relevance in a Dutch sample, as well as Wentworth et al 10 in an American group.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations